Efficiency of criminal proceedings and their cost - Orfin, Agnieszka (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
To sum up, it should be stated that the concept of efficiency should be understood as a quick, effective and rational operation of the participants in the proceedings, taking into account the principles of efficiency and savings of financial resources. The length of proceedings is one of the most acute problems not only of criminal law, but also of the administration of justice in general. The first and foremost reason for such a classification is that the excessive length of proceedings prevents a fair hearing, since it does not respect the constitutional right to have a case heard without undue delay. Secondly, long proceedings generate high costs, an issue particularly important when these costs are borne by the State Treasury and thus not by the convict whose culpable behavior has caused them to arise.The issues of efficiency of criminal proceedings and their costs are inextricably linked. Furthermore, it establishes that the efficiency of criminal proceedings determines the level of generated costs. The research shows that the quality of the proceeded cases depends on the financial outlays and that the costs indicated by the procedural authorities do not correspond with those actually incurred. In conclusion, it should be pointed out that financial aspects fall within the scope of the regulatory impact assessment and constitute a priority when im-plementing new legal provisions, in direct relation to the economic analysis of law and the efficiency and costs of ongoing proceedings.